1996
DOI: 10.1074/jbc.271.49.31106
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian Homolog of Suppressor-of-white-apricot Regulates Alternative mRNA Splicing of CD45 Exon 4 and Fibronectin IIICS

Abstract: We have previously described human (HsSWAP) and mouse (MmSWAP) homologs to the Drosophila alternative splicing regulator suppressor-of-white-apricot (su(w a ) or DmSWAP). DmSWAP was formally defined as an alternative splicing regulator by studies showing that it autoregulates splicing of its own pre-mRNA. We report here that mammalian SWAP regulates its own splicing, and also the splicing of fibronectin and CD45. Using an in vivo system of cell transfection, mammalian SWAP regulated 5 splice site selection in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 54 publications
(55 reference statements)
6
42
0
Order By: Relevance
“…It has recently been shown using a CD45 minigene containing only alternative exon 4 that overexpression of hsSWAP, SF2/ASF, SC35, SRp40, and SRp75 all promoted exclusion of exon 4, which is in agreement with our findings (57,58). Lemaire et al (58) also demonstrated that regulation of CD45 exon 4 splicing is dependent on exon 4 itself and not affected by the presence of the 3Ј constitutive exon, exon 7.…”
Section: Discussionsupporting
confidence: 92%
“…It has recently been shown using a CD45 minigene containing only alternative exon 4 that overexpression of hsSWAP, SF2/ASF, SC35, SRp40, and SRp75 all promoted exclusion of exon 4, which is in agreement with our findings (57,58). Lemaire et al (58) also demonstrated that regulation of CD45 exon 4 splicing is dependent on exon 4 itself and not affected by the presence of the 3Ј constitutive exon, exon 7.…”
Section: Discussionsupporting
confidence: 92%
“…2C). It should be noted that overexpression of CLKs does not change the splicing patterns of other minigenes (data not shown), e.g., GABA A ␥2 alternative 24-nt exon (Ashiya and Grabowski, 1997), clathrin light-chain B exon EN (Stamm et al, 1992, insulin receptor exon 11 (Kosaki and Webster, 1993), and SWAP exon 2A (Sarkissian et al, 1996). Only with the SRp20 exon 4 was a similar effect on exon skipping found (Stoss et al, 1999).…”
Section: Mclk1-4 Promote Skipping Of Tau Exon 10mentioning
confidence: 88%
“…However, previous studies have demonstrated the increased expression of several members of the SR family of general splicing factors upon T-cell activation (28,46). SR proteins have been implicated in the regulation of many alternative splicing events (16,32) and have been shown to influence CD45 alternative splicing in a heterologous system (28,43). Therefore, it is possible that increased synthesis of SR proteins is a required step in the pathway between T-cell activation and CD45 alternative splicing.…”
Section: Discussionmentioning
confidence: 99%